2000
DOI: 10.1021/ja993618l
|View full text |Cite
|
Sign up to set email alerts
|

Metal−Metal Bonding in Rh2(O2CCF3)4:  Extensive Metal−Ligand Orbital Mixing Promoted by Filled Fluorine Orbitals

Abstract: He I and He II gas-phase photoelectron spectra of Rh2(O2CCF3)4 are reported. The electron configuration of the metal−metal bond of Rh2(O2CCF3)4 is determined to be σ2 π4 δ2 δ*2 π*4 with an ionization energy order of σ ≈ π > δ > δ* ≈ π*. The δ* and π* ionization energies are similar within the range of vibrational energy separations. Assignment of the Rh−Rh δ ionization is assisted by previous observations that ionizations from δ orbitals in M2(O2CCF3)4 (M = Mo, W) and Mo2(O2CH)4 show enhanced intensity over io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…318 The fourteen metal-based electrons are predicted by DFT calculations to occupy the Rh-Rh bonding orbitals in the following order of increasing energy: 2 4 2 * 2 * 4 . The PES (both He(I) and He(II)) supports this, with the * (9.55 eV) and * (9.77 eV) ionizations being so close that their vibrational spreads overlap.…”
Section: Miscellaneous Other Pes Resultsmentioning
confidence: 99%
“…318 The fourteen metal-based electrons are predicted by DFT calculations to occupy the Rh-Rh bonding orbitals in the following order of increasing energy: 2 4 2 * 2 * 4 . The PES (both He(I) and He(II)) supports this, with the * (9.55 eV) and * (9.77 eV) ionizations being so close that their vibrational spreads overlap.…”
Section: Miscellaneous Other Pes Resultsmentioning
confidence: 99%
“…34 From the photoelectron spectroscopy point of view augmented by density functional calculations (DFT/BLYP), it can only be concluded that the δ* and π* ionization energies are similar within the spread of vibrational energies with excitation (0.2 eV). 35 Herein, we performed calculations by using the DFT level of theory with the new hybrid parameters free exchange-correlation functional PBE0 that is successfully used for modeling transition metal clusters. 36 Our results support a ground-state configuration of σ 2 π 4 δ 2 π* 4 δ* 2 for [Rh 2 (O 2 CCF 3 ) 4 ] (Supporting Information, Figure S33).…”
Section: Resultsmentioning
confidence: 99%
“…Metal±metal interactions are central to the behavior of a wide variety of molecules, clusters, interfaces, and materials. Our interest in the bonding of metal atoms to each other has led us to examine the electronic structures of numerous such systems via gas-phase photoelectron spectroscopy (Lichtenberger et al, 1999(Lichtenberger et al, , 2000. Part of this effort has been focused on understanding the effect of substitution of functional groups at the phenyl rings of the diphenylformamidinate ligand on the electronic structure of metal±metal bonded systems as a whole.…”
Section: Commentmentioning
confidence: 99%
“…Data collection: CAD-4 Operations Manual (Enraf±Nonius, 1977); cell re®nement: CAD-4 Operations Manual; data reduction: MolEN (Fair, 1990); program(s) used to solve structure: SHELXS97 (Sheldrick, 1997); program(s) used to re®ne structure: SHELXL97 (Sheldrick, 1997); molecular graphics: SHELXTL (Bruker, 1997); software used to prepare material for publication: SHELXTL. Our interest in the bonding of metal atoms to each other has led us to examine the electronic structures of numerous such systems via gas-phase photoelectron spectroscopy (Lichtenberger et al, 1999(Lichtenberger et al, , 2000. Part of this effort has been focused on understanding the effect of substitution of functional groups at the phenyl rings of the diphenylformamidinate ligand on the electronic structure of metal-metal bonded systems as a whole.…”
Section: Re®nementmentioning
confidence: 99%